Single nucleotide variations in the buffalo kappa-casein gene (CSN3) - Stafuzza, Nedenia B. [UNESP] (2013)
Caseins are the major milk proteins associated with lactation performance, milk composition and cheese yield efficiency, representing around 80% of the total amount of proteins found in milk. Among the caseins, kappa-casein is the protein that stabilizes micelle structure during milk coagulation process and being used during the cheese production. The kappa-casein gene (CSN3) has been previously mapped to buffalo chromosome 7 using a radiation hybrid panel and a comparative map was established using the sequence from bovine chromosome 6. The molecular structure of this gene has also been established in river buffalo, with a total length of 13,191 bp (GenBank: AM900443.1) and containing five exons. In this study we searched for single nucleotide variations in specific regions of the CSN3 gene in three animals representing the Murrah breed. Sequencing reactions were performed using ABI3730xl sequencer. The primer walking method was used to span the 5'-UTR and intron 2 regions of the gene, for which ten primer pairs were designed using Oligo 6 software. BLAST tool was used to verify the primers specificity. DNA sequences assemblies from all three animals were performed with Sequencher® software 4.1, while multiple alignments were performed using Clustal W software to identify single nucleotide variations. The sequencing revealed a total of 19 single nucleotide variations with 13 located in the upstream regulatory region of the gene (5'-UTR) and six on intron 2. These variations can be validated using commercial populations segregating specific economic traits.